Регресійні залежності вартісних показників елементів електричних мереж напругою 10-35 кВ - Буйний, Роман Олександрович; Перепечений, Віталій Олександрович; Зорін, Владлен Володимирович (НТУ "ХПІ", 2017)
Обґрунтування заходів зі зменшення технологічних витрат електричної енергії потребує достовірних вартісних показників. Автори дослідили зміну вартості кабельно-провідникової продукції від її перерізу, а також вартості трансформаторів від їх номінальної потужності та отримали відповідні регресійні залежності для напр уг 10, 20 та 35кВ. Дані залежності можуть бути використані для аналітичного розв’язку оптимізаційних задач.

Reliable cost estimates are necessary to justify the technological measures aimed at reducing power losses in electric power networks. It is of particular importance for the 10-35kV networks in Ukraine and CIS countries. The authors analyzed large amounts of the relevant data and concluded that facilities costs are nearly linear functions of voltage class. The following cost dependencies are built and analyzed: cost of oil transformers vs rated apparent power, cables with XLPE insulation vs their cable cross sectional area and screen area, and ACSR conductors overhead lines vs cross sectional area. The corresponding regression lines for voltages of 10, 20 and 35 kV were also built and the quality of approximation is estimated with the coefficient of determination and mean-square error. More than 97% of variation in transformer costs is explained by their rated apparent power, more than 99% of variation in cable with XLPE insulation - by cross sectional area and screen area, and more than 99% of variation in the cost of ACSR conductors – by their cross sectional area. These results can be used to analytically solve the optimization problems and to justify the technological measures aimed at reducing power losses in medium voltage electric power networks.
Regression relationships for costs of facilites in electrical power networks 10- 35 kV
Keywords: вартісні показники; трансформатори; проводи; кабелі; регресійні залежності; коефіцієнт детермінації; середньоквадратична похибка; cost parameters; transformers; wires; cables; depending regression; coefficient of determination; mean-square error